Heritability of Directional Asymmetry in Drosophila melanogaster. (23rd August 2009) - Carter, Ashley J. R.; Osborne, Elizabeth; Houle, David
Abstract : Directional asymmetry (DA), the consistent difference between a pair of morphological structures in which the same side is always larger than the other, presents an evolutionary mystery. Although many paired traits show DA, genetic variation for DA has not been unambiguously demonstrated. Artificial selection is a powerful technique for uncovering selectable genetic variation; we review and critique the limited number of previous studies that have been performed to select on DA and present the results of a novel artificial selection experiment on the DA of posterior crossvein location in Drosophila wings. Fifteen generations of selection in two genetically distinct lines were performed and none of the lines showed a significant response to selection. Our results therefore support and reconfirm previous findings; despite apparent natural variation and evolution of DA in nature, DA remains a paradoxical trait that does not respond to artificial selection.